Association between proteinuria and incident colorectal cancer: analysis of a nationwide population-based database. Issue 4 (4th April 2022) - Matsuoka, Satoshi; Kaneko, Hidehiro; Okada, Akira; Fukui, Akira; Yano, Yuichiro; Itoh, Hidetaka; Morita, Kojiro; Fujiu, Katsuhito; Michihata, Nobuaki; Jo, Taisuke; Takeda, Norifumi; Morita, Hiroyuki; et al.
Abstract : Objectives: This study aimed to assess whether adults with proteinuria were at a higher risk of incident colorectal cancer (CRC) than those without proteinuria using a large-scale population-based database. Design: A retrospective observational study. Setting: The JMDC Claims Database, an administrative health claims database, was used. Data were collected between 2005 and 2020. Participants: We selected records of participants (n=3 543 705) who underwent health check-ups, including physical examinations, blood tests and urine dipstick tests. We excluded participants who were aged <20 years (n=25 577), had a history of CRC, colorectal disease, renal disease and renal replacement therapy (n=114 888), or had missing data on medications (n=170 145), cigarette smoking (n=14 835), alcohol consumption (n=366 414) or physical activity (n=106 550). Finally, we analysed 2 745 296 participants. Main outcome measures: The primary outcome was CRC at any stage. Results: Participants were categorised as having no proteinuria (n=2 435 872), trace proteinuria (n=231 153) or positive proteinuria (n=78 271). Over a mean follow-up period of 1189±914 days, 10 615 CRC diagnoses were recorded. The incidence of CRC (95% CI) was lowest in participants without proteinuria (11.7; 95% CI, 11.5 to 11.9 per 10 000 person-years), followed by trace proteinuria (12.5; 95% CI, 11.7 to 13.3 per 10 000 person-years) and positive proteinuria (16.1; 95% CI, 14.6 to 17.7 per 10 000 person-years). After multivariable adjustment, compared with no proteinuria, HRs for incident CRC were 1.20 (95% CI, 1.12 to 1.29) and 1.23 (95% CI, 1.11 to 1.36) for trace and positive proteinuria, respectively. The association between proteinuria and incident CRC existed in participants after multiple imputations for missing data, with a follow-up period of ≥365 days, regardless of age, sex, obesity, hypertension, diabetes mellitus and estimated glomerular filtration rate. Conclusions: Trace and positive proteinuria were associated with a greater risk of incident CRC. Assessment of proteinuria could help identify individuals at an increased risk of CRC.